Public Service Delivery in the Era of Digital Governance : Case Studies from Indonesia - Karippacheril, Tina George (World Bank, Washington, DC, 2016)
In an era of digital governance, information technology, internet, mobile devices, and social media have transformed the organization, management, and delivery of public services. Developing country governments around the world are gradually replacing paper-based processing and delivery with next-generation technologies to serve citizens. In Indonesia, a host of citizen-led approaches have emerged ahead of government process transformation efforts. This global expert team (GET) note examines case studies of digital-era governance (DEG), a concept put forward by Dunleavy, further developed by means of examples from Indonesia focusing on demand-side approaches to stimulate improvements in public sector performance.